The Effect of Financial Distress, and Audit Opinion in The Previous Year on The Acceptance of Going Concern Audit Opinion with The Covid-19 Pandemic as a Moderation Variable - Putri, Hardianti Eka; Meini, Zumratul; Digdowiseiso , Kumba (CV ODIS, 2023)
This study aims to empirically examine the effect of financial distress and audit opinions in the previous year on the receipt of going concern audit opinions during the current Covid-19 pandemic conditions in manufacturing companies in the basic industrial and chemical sectors and various industries listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The technique used in sampling this study is by purposive sampling method taken based on certain criteria. The number of samples used was 48 companies observing 240 samples during the 2016-2020 research period. This study used the help of the spss program version 25 with the logistic regression analysis method. The results of this study show that the variables of financial distress and audit opinion of the previous year have a positive and significant effect on the acceptance of going concern audit opinion. The moderation variable of the COVID-19 pandemic cannot affect the relationship between financial distress and going concern audit opinions. The COVID-19 pandemic was unable to moderate the relationship between the previous year's audit opinion and the going concern audit opinion.